Theoretical and Methodological Foundations of The Linguistic Study of Monologue - Ikromova Gulhida Ahmadillo kizi (European International Journal of Pedagogics, 2025)
This study provides a comprehensive analysis of the linguistic, communicative, and semiotic features of the dramatic monologue. As a complex form of character speech, the dramatic monologue serves not only to express inner experiences but also to develop dramatic action, deepen conflict, and directly influence the audience or reader. The paper examines the relationship between monologue and dialogue, highlighting its hidden dialogic nature and orientation toward an addressee. It also analyzes the syntactic, semantic, and pragmatic characteristics of monologue, particularly psychological states expressed through modality, ellipsis, rhetorical questions, and pauses. Based on approaches in world and Uzbek linguistics and literary studies (Bakhtin, Galperin, Pfister, and others), the study reveals the multilayered and polysystemic nature of the dramatic monologue. As a result, the dramatic monologue is interpreted as an essential component of dramatic discourse and as a psycholinguistic and linguopoetic phenomenon.